Probiotics: Their Potential to Impact Human Health - Sanders, Mary Ellen; Gibson, Glenn; Gill, Harsharnjit S.; Guarner, Francisco (Council for Agricultural Science and Technology (CAST), 2007)
Controlled human studies have revealed a diverse range of health benefits from consumption of probiotics, due largely to their impact on immune function or on microbes colonizing the body. This publication reviews the literature on probiotics, describes the characteristics of probiotics, discusses the microbes that colonize the human body, and explains how probiotics can treat and prevent disease. The paper also addresses safety issues of probiotic use, suggests future developments, and provides research and policy recommendations.